The Peripheral Culture Museum and its articulations: perspectives of an organic intellectual about Brazilian Sociomuseology (Cadernos de Sociomuseologia, 2023)
Viviane Conceição Rodrigues is an important Brazilian organic intellectual. Born in 1982on the outskirts of Maceió, it became part of a series of networked cultural articulations and was fundamental element in the founding of the Peripheral Culture Museum, one of the 12 Memory Spots Pioneers, headquartered in the Jacintinho neighborhood. An award-winning Afro-entrepreneur, she has a degree in Public Relations from the Federal University of Alagoas (UFAL, 2008) and Master from the Universidad Pablo de Olavid (2020), in Spain. His personal trajectory mixes with the trajectory of Brazilian comunity museums, spreading out in territories far beyond the geographic, having participated in the constitution of a set of public policies for the field of Museology in Brazil. In an interview granted to us, generous, affectionate and patient, shared fundamental aspects for thinking Sociomuseology through the hands of those who live on the border between academia and social militancy, in a constant flux between putting into practice in favor of the community the most complex popular and scientific reflections in a way connected.